Digest of Narcotic Drugs and Psychotropic Substances Act, 1985 : alongwith Prevention of Illicit Traffic in Narcotic Drugs and Psychotropic Substances Act, 1988, and Opium Act, 1878 - Abidi, S. H. S. (Modern Law House, 1999)
Digest of case-law on the enactments mentioned above.